Organización contable en la empresa del Sr. Herrera Guerrero Augusto Giovanny del Cantón Catamayo, periodo del 01 de abril al 30 de junio del 2023. - Ochoa Rojas, Anjhy Stefanie (2024)
The Curricular Integration Work called Accounting Organization in the Company of Mr. Herrera Guerrero Augusto Giovanny of Catamayo Canton, period from April 01 to June 30, 2023 is oriented to organize and propose accounting tools, in such a way that facilitates the owner the generation of accounting information, and thus to know with certainty the economic and financial situation of the company in order to make the correct decision making to improve the performance of the same. In order to comply with the first objective of the curricular integration work, the accounting process began with the design of a plan and manual of accounts according to the needs of the company, with their description and respective codification to facilitate the registration of operations, the initial inventory by means of the physical verification of the goods, values and obligations that the company owns with an asset value of US$ 524.871,78, its liabilities of US$ 33.647,69 and a capital of US$ 491.224,09 dollars; the preparation of the Initial Situation Statement, detailing the accounts of assets, liabilities and equity; the Daily Book, recording the transactions in chronological order, the General Ledger, the Trial Balance, the Work Sheet until obtaining the Financial Statements, such as the Income Statement, the Statement of Financial Position and the Cash Flow Statement; For the development of the same the multiple account or periodic inventory system was used, with the purpose of being able to register and control the movement of the inventory of the company; allowing to obtain the detailed information in each one of the accounts that intervene in this system, thus at the end of the accounting period to know if there is a gross profit or loss in sales. Finally, main records and auxiliary formats were designed, such as: auxiliary of purchases, sales, consumption, depreciations, payment roles and provisions; where the financial and economic information of the entity has been detailed and consolidated, facilitating and simplifying the registration of the transactions that are carried out daily in the company. Given the conclusion of the accounting process and the issuance of the respective financial statements, the company Herrera Guerrero Augusto Giovanny presents during the accounting period in the Income Statement obtaining as results a profit of $ 4,118.86, so this business is shown as a solid and competitive company within the sector it operates, obtaining a great profitability due to the increase of its sales, being a significant information for its owner and based on this, make appropriate decisions for the continued economic growth of the commercial enterprise.